Bioactivity and bioaccessibility of novel rutin-protein composites incorporated into a functional dairy beverage : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Palmerston North, New Zealand - Singh, Anubhavi (Massey University, 2022)
Rutin, a plant-derived bioactive compound is becoming increasingly popular as a natural ingredient in various nutraceutical, pharmaceutical, or cosmetic industries. However, because of its hydrophobic nature, rutin possesses a low solubility in both aqueous- and lipid-based systems; thereby, reducing its absorption in the gastrointestinal digestion tract. Such properties of rutin (i.e., poor solubility and low bioavailability) have been the main limiting factors against its use as a functional ingredient in the food industry so far. Pertaining to its functional attributes for exhibiting anti-oxidative potency coupled with its metabolic capacity that regulates cellular functions in the physiological system, previous research at Massey University invented a highly soluble form of rutin using a food protein (sodium caseinate). This delivery system safeguards rutin against undesirable changes that occur during the processing and storage of the food, as well as under the conditions of the upper part of the gastrointestinal system. This patented novel technology, known as ‘FlavoPlus’ existing in the form of two products (FlavoPlus 1™ and FlavoPlus 2™), can deliver rutin at the targeted sites in the gut and can substantially improve its bioavailability. Accordingly, the current research used FlavoPlus™ as a functional ingredient for the assessment of its functionality (bioactivity and bioaccessibility of rutin) in a protected form after its incorporation into a functional milk beverage. This study also aimed to assess the antioxidant capacity and the subsequent absorption using a Caco-2 cell model system. This research was carried out in two phases. In Phase 1, the antioxidant potential of FlavoPlus 1 (FP1), FlavoPlus 2 (FP2), and rutin hydrate (RH) was investigated using DPPH (2,2- diphenyl-1-picryl-hydrazyl) assay, which attributed to the total antioxidant content present in these three samples. FP1 and FP2 had significantly (p≤0.05) higher scavenging abilities in a concentration-dependent manner than RH. Further, the total phenolic content (TPC) in FP1, FP2, and RH was measured by corresponding each concentration with rutin equivalent present in the three samples. RH consisted of 94% rutin equivalent per gram of sample whereas FP1 and FP2 had 46% and 27.3% rutin equivalent per gram of sample, respectively. Although RH contained higher rutin content (%), its antioxidant activity was lower than FP1 at 200 µg/mL. Further, FP1, FP2, and RH were subjected to an in vitro cell-based model to measure their cell viability and intracellular antioxidant potency using Caco-2 cells that were stimulated with 0.1% DMSO. With an increase in their concentration, FP1 and FP2 maintained cell viability better than RH after four hours of incubation. As there were no significant (p>0.05) differences in cell viability, it was proposed that FP1 and FP2 protected Caco-2 cells without causing any toxicity even at higher concentrations. In addition, the intracellular antioxidant assay proposed that FP1 and FP2 exhibited higher antioxidative potency even at a low concentration of 0.5 µg/mL than RH in Caco-2 cells that were stimulated with a free radical generator (i.e., 2,2′- azobis(2-methylpropionamidine) dihydrochloride (AAPH)) during 0, 10, and 30 minutes of incubation. Thus, similar attributes were analysed after exposing FP1, FP2, and RH to in vitro gastrointestinal digestion, to understand the interactions between rutin-protein composites and the dairy beverage matrix. In Phase 2, the rutin-protein composites and RH were incorporated into a dairy beverage to deliver rutin in the gut. Bigger particle size was observed for FP2 during both gastric and intestinal phases, when compared to FP1, thereby reducing the surface area. Whereas RH showed a decreasing trend for particle size from gastric to intestinal phase, which could be due to the aggregation of proteins as the result of pH change during both gastric and intestinal phases. Moreover, the bioaccessibility of FP1 and FP2 after digestion was estimated at 63% and 45%, respectively. These bioaccessible samples were subjected to transepithelial electrical resistance (TEER) estimation. The findings suggested that FP2 maintained the barrier integrity of Caco-2 cell monolayers even at high concentrations over 24 hours of incubation whereas, FP1 had a lower TEER value suggesting a disruption in the epithelial barrier. These results are in accordance with the findings obtained from the cell viability assay as FP1 and FP2 maintained the viability within a similar range of concentrations. In addition, the intracellular antioxidant assay proposed that FP2 exhibited higher antioxidant potency than either FP1 or RH during 0 and 10 minutes of incubation. With a longer incubation period, FP1 was stronger in scavenging AAPH even at a higher concentration of 25 µg/mL. Taken together, the findings of this research confirmed that both FlavoPlus products could be delivered through a suitable dairy matrix (i.e., a milk beverage) as the carrier that attributes their high digestibility and enhanced functional properties within the gut without compromising human health and nutrition. Thus, based on the findings of this research, it can be concluded that FP1 and FP2 showed higher bioactivity than RH based on their antioxidant potential and cell viability of Caco-2 cells. The rutin-protein composites exhibited higher bioaccessibility when delivered through a dairy matrix and were found to be non-toxic to Caco-2 cells at higher concentrations resulting in good barrier integrity for Caco-2 monolayers. However, further research is required to assess the bioavailability of rutin-protein composites after digestion within physiological systems in vivo.
Figure 2.1 is reproduced with permission.